Comparability of a provisioned device versus bring your own device for completion of patient-reported outcome measures by participants with chronic obstructive pulmonary disease: qualitative interview findings - Louise Newton; Oliver Knight-West; Sonya Eremenco; Stacie Hudgens; Mabel Crescioni; Tara Symonds; David S. Reasner; Bill Byrom; Paul O'Donohoe; Susan Vallow; the Patient-Reported Outcome (PRO); Electronic Clinical Outcome Assessment (eCOA) (SpringerOpen, 2022)
Abstract Background There is interest in participants using their own smartphones or tablets ("bring your own device"; BYOD) to complete patient-reported outcome (PRO) measures in clinical studies. Our study aimed to qualitatively evaluate participants' experience using a provisioned device (PD) versus their own smartphone (BYOD) for this purpose. Methods Participants with chronic obstructive pulmonary disease (COPD) were recruited for this observational, cross-over study and completed PRO measures daily on one device type for 15 days, then switched to the other device type to complete the same measures for another 15 days. After each 15-day period, semi-structured interviews were conducted about their experience with the device. Results Of 64 participants enrolled, the final qualitative analysis populations comprised those who participated in an interview without protocol violations. Thus, the qualitative longitudinal population (LP) included n = 57 (89%), while the qualitative cross-sectional population (CSP) included n = 60 (94%). CSP participants found both device types easy to use. Twenty CSP participants (33%) reported missing data entry on at least one day when using PD, and 24 (40%) reported missing at least one day when using BYOD. In the LP, preference for one of the device types was somewhat evenly split; 45.6% (n = 26) preferred PD and 50.9% (n = 29) preferred BYOD. The most common reason for preferring PD was that it was "dedicated" to the study; the "convenience" of carrying a single device was the main reason for preferring BYOD. Conclusion The findings from the interviews demonstrated few differences in participants' experience completing PRO measures on a PD versus BYOD. Our study supports the use of BYOD as a potential addition to PD for collecting PRO data and contributes evidence that BYOD may be employed to collect PRO data in demographically diverse patient populations.